2022
DOI: 10.5194/acp-22-9703-2022
|View full text |Cite
|
Sign up to set email alerts
|

Oxygenated volatile organic compounds (VOCs) as significant but varied contributors to VOC emissions from vehicles

Abstract: Abstract. Vehicular emissions are an important source for volatile organic compounds (VOCs) in urban and downwind regions. In this study, we conducted a chassis dynamometer study to investigate VOC emissions from vehicles using gasoline, diesel, and liquefied petroleum gas (LPG) as fuel. Time-resolved VOC emissions from vehicles are chemically characterized by a proton-transfer-reaction time-of-flight mass spectrometer (PTR-ToF-MS) with high frequency. Our results show that emission factors of VOCs generally d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 73 publications
(80 reference statements)
1
9
0
Order By: Relevance
“…NO + PTR-ToF-MS was also applied to measure cycloalkane emissions along with other organic compounds from vehicles using gasoline, diesel, and liquified petroleum gas (LPG) as fuel, by conducting a chassis dynamometer measurement (Wang et al, 2022b). Figure 7 shows the time series of C 12 cyclic and bicyclic alkanes, C 12 alkanes, toluene, and acetaldehyde measured by NO + PTR-ToF-MS for a gasoline vehicle with emission standard of China III and a diesel vehicle with emission standard of China IV.…”
Section: Applications In Ambient Air and Vehicular Exhaustsmentioning
confidence: 99%
See 2 more Smart Citations
“…NO + PTR-ToF-MS was also applied to measure cycloalkane emissions along with other organic compounds from vehicles using gasoline, diesel, and liquified petroleum gas (LPG) as fuel, by conducting a chassis dynamometer measurement (Wang et al, 2022b). Figure 7 shows the time series of C 12 cyclic and bicyclic alkanes, C 12 alkanes, toluene, and acetaldehyde measured by NO + PTR-ToF-MS for a gasoline vehicle with emission standard of China III and a diesel vehicle with emission standard of China IV.…”
Section: Applications In Ambient Air and Vehicular Exhaustsmentioning
confidence: 99%
“…For instance, the determined emission factors of C 12 cyclic alkanes are 0.06 mg km −1 for gasoline vehicles and 1.17 mg km −1 for diesel vehicles. In addition to cycloalkanes and alkanes, other compounds including aromatics and oxygenated VOCs also demonstrate large differences between gasoline and diesel vehicles, which were mainly attributed to different chemical compositions of gasoline and diesel fuels (Wang et al, 2022b). Recent studies reported that cyclic compounds occupied a large proportion of IVOCs emitted from vehicles, with prominent SOA formation potentials (Fang et al, 2021;Huang et al, 2018;Zhao et al, 2016), but emissions of individual cycloalkanes have not been not reported yet.…”
Section: Applications In Ambient Air and Vehicular Exhaustsmentioning
confidence: 99%
See 1 more Smart Citation
“…The primary sources for the aldehydes are anthropogenic (mostly from vehicular emission) and biogenic (mainly from vegetation), whereas the secondary sources include the photochemical reactions of VOCs emitted from man-made and natural activities. [41][42][43][44][45] Besides OH radicals, Cl atoms and NO 3 , CH 2 OO was found to have considerably larger rate coefficients with aldehydes. For example, the rate coefficient obtained for the CH 2 OO + CH 3 CHO reaction was (9.5 AE 0.7) Â 10 À13 cm 3 molecule À1 s À1 at 298 K and 4 torr by direct kinetic measurement using photoionization mass spectrometry (PIMS) by Taatjes et al, 31 but it was reported to be (1.48 AE 0.04) Â 10 À12 cm 3 molecule À1 s À1 at 295 K and 25 torr by indirect measurement of the CH 2 OO concentration by Stone et al 13 Similar results were obtained in other studies by Berndt et al 46 and Elsamra et al 47 The reaction mechanism predicted for the CH 2 OO with acetaldehyde is the formation of a secondary ozonide (SOZ), which undergoes 1,5-internal Htransfers from either of the carbon atoms to form hydroxyethyl formate (HEF) and hydroxymethyl acetate (HMA).…”
Section: Introductionmentioning
confidence: 98%
“…Except for molecules with negligible photochemical reactivity, volatile organic compounds (VOCs) are carbon compounds that engage in atmospheric photochemical processes. , Most of them are highly poisonous, carcinogenic, and dangerous, which bring significant destruction to the nature environment. Styrene (C 8 H 8 ) is a representative aromatic hydrocarbon among the VOCs.…”
Section: Introductionmentioning
confidence: 99%